Misconception contributed to COVID-19 vaccine hesitancy in patients with lung cancer or ground-glass opacity: a cross-sectional study of 324 Chinese patients - Weitao Zhuang; Jingyu Zhang; Peijian Wei; Zihua Lan; Rixin Chen; Cheng Zeng; Qiuling Shi; Guibin Qiao (Human Vaccines & Immunotherapeutics, 2021)
Patients highly vulnerable for COVID-19 infection have been proposed to take priority for vaccination. However, vaccine hesitancy is usually more prevalent in these patients. Investigation around modifiable contributors of vaccine hesitancy plays a pivotal role in the formulation of coping strategies. We aimed to evaluate the impact of vaccine misconception in patients with lung cancer or pulmonary ground-glass opacity (GGO). A web-based questionnaire was constructed based on a qualitative interview with 15 patients and reviewed by a multidisciplinary expert panel. Six Likert five-scale questions were used to generate a score of vaccine misconception (SoVM), which ranged from 0 to 24 points, with a higher score indicating a higher level of misconception. A total of 61.6% (324/526) patients responded to our questionnaire. A higher proportion of low willingness patients (n = 173), compared to high willingness patients (n = 151), disagreed that cancer patients should be prioritized for COVID-19 vaccination (82.1% vs. 50.3%, p < .001) and perceived themselves to have contraindications (45.7% vs. 15.9%, p < .001). The mean SoVM was significantly lower in the high willingness group than the low willingness group (9.9 vs. 13.0, p < .001). Among the unvaccinated patients, the SoVM increased as the willingness to be vaccinated decreased (p < .0001). In multivariable logistic regression, patients with higher SoVM (OR 0.783, 95% CI 0.722–0.848), being female (OR 0.531, 95% CI 0.307–0.918) or diagnosed with lung cancer (OR 0.481, 95% CI 0.284–0.814) were independently associated with a lower willingness to be vaccinated against COVID-19. Receiver operating characteristic curve suggested that a SoVM of 11 yielded the best discrimination for predicting the willingness to receive COVID-19 vaccine (AUC = 0.724). The study findings reveal that patient misconception significantly contributes to vaccine hesitancy and needs to be addressed by evidence-based education tailored to their specific concerns.